2014
DOI: 10.1021/jz402625z
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organized Traveling Chemo-Hydrodynamic Fingers Triggered by a Chemical Oscillator

Abstract: Pulsatile chemo-hydrodynamic patterns due to a coupling between an oscillating chemical reaction and buoyancy-driven hydrodynamic flows can develop when two solutions of separate reactants of the Belousov−Zhabotinsky reaction are put in contact in the gravity field and conditions for chemical oscillations are met in the contact zone. In regular oscillatory conditions, localized periodic changes in the concentration of intermediate species induce pulsatile density gradients, which, in turn, generate traveling c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…10,11 It would be very nice to be able to couple viscous e ects with the canonical oscillating Belousov-Zhabotinky reaction around an A + B → oscillator con guration. 17 While coupling of BZ localized oscillations in this con guration has already been done successfully for buoyancy-driven e ects, 16,24 it still remains to see how to obtain large viscosity changes in the BZ system. We hope that the current work will trigger future e orts in this direction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 It would be very nice to be able to couple viscous e ects with the canonical oscillating Belousov-Zhabotinky reaction around an A + B → oscillator con guration. 17 While coupling of BZ localized oscillations in this con guration has already been done successfully for buoyancy-driven e ects, 16,24 it still remains to see how to obtain large viscosity changes in the BZ system. We hope that the current work will trigger future e orts in this direction.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Chaos ARTICLE scitation.org/journal/cha Recently, special attention has been put on understanding how localized temporal oscillations of chemical concentrations can also actively couple to hydrodynamic ows to produce pulsatile ows. [16][17][18] Localized oscillations 19 or stationary Turing patterns 20,21 can be obtained in autocatalytic reactions around A + B → oscillator fronts when putting in contact two zones containing separate reactants A and B of an oscillatory reaction. 17,18,22,23 From the theoretical point of view, it has been shown that localized oscillations and Turing structures can interact with buoyancy-driven ows when the reactants A and B of the oscillatory Brusselator model are initially separated, meet by di usion, and produce the intermediate X and Y species locally, which changes the density.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments putting into contact active media have been recently reported where the reagents of the chemical oscillator, the Belousov-Zhabotinsky reaction, have been initially separated into two adjoined parts 8,9 . For instance the interaction of Turing and Hopf bifurcations can produce mixed states such as oscillatory Turing patterns or the coexistence of stable local domains supporting different a Université Libre de Bruxelles (ULB), Non-linear Physical Chemistry Unit, Service de Chimie Physique et Biologie Theorique, CP231, Campus Plaine, 1050, Brussels, Belgium; E-mail: jcarball@ulb.ac.be ‡ These authors contributed equally to this work dynamics but also more complex structures such as spatiotemporal chaos 1,3-5 .…”
Section: Introductionmentioning
confidence: 99%
“…For compositional gradients parallel to gravity, let us mention the acidbase reaction with convection due to density effects [7][8][9][10], autocatalytic fronts [11,12], and, recently, oscillating chemical reactions [13]. For a compositional gradient perpendicular to gravity, different reaction schemes have been studied with buoyancy effects [14] as well as Marangoni effects occurring at an interface with another physical domain (e.g., an air layer) which is not involved in the chemical process [15,16].…”
mentioning
confidence: 99%